Pandemic Covid-19: The Opportunities and Challenges to Using ICT in Mathematics Learning - Sabaruddin Sabaruddin; Marzuki Marzuki; Khairunnisak Khairunnisak (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: Social distance arrangements applied in all Indonesian educational institutions and even throughout the world including universities during Covid-19 pandemic. Design/methodology/approach: All teaching and learning activities on campus turn to online learning that uses a variety of teaching media, such as Zoom cloud meetings, WhatsApp groups, and Google classrooms. Findings: The purpose of this study is to see how the opportunities and challenges of using information technology in learning mathematics during covid-19. Research limitations/implications: The approach in this study uses a qualitative approach and type of descriptive research. Intake of research subjects using a purposive technique. . Practical implications: The subjects in this study conduct 8 students of the mathematics education department. The conclusions of this study are 1) The use of mathematics learning technology has been maximally carried out by students through online mathematics learning using various learning platforms. 2) In terms of understanding not all students can adapt to learn mathematics well because students have difficulty in understanding mathematics material through distance learning. 3) Factors that hinder learning are the availability of internet networks and the limitations of internet quotas.. Paper type: This paper is study case type